2023
DOI: 10.1152/ajpheart.00390.2022
|View full text |Cite
|
Sign up to set email alerts
|

A high-sucrose diet exacerbates the left ventricular phenotype in a high fat-fed streptozotocin rat model of diabetic cardiomyopathy

Abstract: Left ventricular (LV) dysfunction is an early, clinically detectable sign of cardiomyopathy in type 2 diabetes mellitus (T2DM) that precedes the development of symptomatic heart failure. Pre-clinical models of diabetic cardiomyopathy are essential to develop therapies that may prevent or delay the progression of heart failure. This study examined the molecular, structural, and functional cardiac phenotype of two rat models of T2DM induced by a high-fat diet (HFD) with a moderate- or high-sucrose content (conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Although not yet extensively studied, dietary interventions high in monosaccharide fructose caused insulin resistance, unchanged or mildly elevated blood glucose, dyslipidemia and notable diastolic function in rodents [ 55 , 56 , 57 ]. Velagic et al demonstrated that cardiac complications were more advanced in STZ-induced diabetic rats on a high-sugar HFD compared with those on a moderate-sugar HFD for 8 weeks, indicating the crucial role of sugars in diet composition in preclinical models for diabetic heart diseases [ 58 ]. Furthermore, elevated myocardial fructose has been shown to be an early cardiac response to diabetes, preceding clinically-detected diastolic dysfunction [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet extensively studied, dietary interventions high in monosaccharide fructose caused insulin resistance, unchanged or mildly elevated blood glucose, dyslipidemia and notable diastolic function in rodents [ 55 , 56 , 57 ]. Velagic et al demonstrated that cardiac complications were more advanced in STZ-induced diabetic rats on a high-sugar HFD compared with those on a moderate-sugar HFD for 8 weeks, indicating the crucial role of sugars in diet composition in preclinical models for diabetic heart diseases [ 58 ]. Furthermore, elevated myocardial fructose has been shown to be an early cardiac response to diabetes, preceding clinically-detected diastolic dysfunction [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinically, diets high in both fat and sucrose have been shown to induce T2DM with LV hypertrophy and diastolic dysfunction in mice after 16 weeks and 17 weeks, respectively [26,27]. Following injection with a pancreatic β-cell toxin, rats that were fed a high-sucrose, HFD displayed worse adverse LV remodeling and diastolic dysfunction compared with moderate-sucrose, HFD-fed rats [28]. To mimic this clinical situation, our research group previously developed a rat model of T2DM induced by a high-sucrose diet or the WD, with adverse cardiac remodeling and cardiac dysfunction [19].…”
Section: Mit and Hiit As Cardioprotective Strategies In The Developme...mentioning
confidence: 99%